Antibacterial Photodynamic Inactivation of Antibiotic-Resistant Bacteria and Biofilms with Nanomolar Photosensitizer Concentrations - Vinagreiro, Carolina dos Santos (2020)
Gram-negative bacteria and bacteria in biofilms are very difficult to eradicate and are the most antibiotic-resistant bacteria. Therapeutic alternatives less susceptible to mechanisms of resistance are urgently needed to respond to an alarming increase of resistant nosocomial infections. Antibacterial photodynamic inactivation (PDI) generates oxidative stress that triggers multiple cell death mechanisms that are more difficult to counteract by bacteria. We explore PDI of multidrug-resistant bacterial strains collected from patients and show how positive charge distribution in the photosensitizer drug impacts the efficacy of inactivation. We demonstrate the relevance of size for drug diffusion in biofilms. The designed meso-imidazolyl porphyrins of small size with positive charges surrounding the macrocycle enabled the inactivation of bacteria in biofilms by 6.9 log units at 5 nM photosensitizer concentration and 5 J cm-2, which offers new opportunities to treat biofilm infections.